Studi Literatur Studi Literatur Tentang Pengaruh Kepemimpinan Intruksional Kepala Sekolah, Budaya Kerja terhadap Kinerja Guru - Rosa Linda Novitasari; Nunuk Hariyati; Syunu Tri Hantoyo; Ayu Wulandari; Kaniati Amalia; Amrozi Khamidi; Mochamad Nur Salim (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research focuses on the influence of principals' instructional leadership and work culture on teacher performance through a literature study approach. This research method uses a literature study method with a narrative review model. The research results show that effective instructional leadership from the principal has a positive impact on teacher performance and effective instructional leadership from the principal creates a better work culture. With good instructional leadership, school principals can encourage improvements in teacher performance through appropriate supervision, direction, and support. In conclusion, showing that the influence of instructional leadership is significant in building a positive work culture and supporting increased quality of performance in the school environment. Keywords: instructional leadership, teacher performance, work culture.